Perlindungan Hukum Terhadap Perusahaan Asuransi Atas Adanya Penyalahgunaan Klaim Asuransi - Edi Wahjuni; Rhama Wisnu Wardhana; Safira Oktavia Purwanto (Universitas Islam Darul Ulum, 2023)
insurance that is starting to grow chosen by the public is property insurance. Property insurance is a product that provides compensation in the event of damage to the insured property. The purpose of writing this study is to analyze the forms of abuse of insurance claims and forms of legal protection for insurance companies from abuse of claims. The method is a normative juridical research type. The problem approach used is the legal approach (state approach) and the conceptual approach (conceptual approach). Based on the results of the study, The existence of misuse of insurance claims by unscrupulous company leaders who bring losses in payment of claims by insurance companies is a form of unlawful act as regulated in the provisions of Article 1365 of the Civil Code. Then, the form of legal protection for insurance companies from losses due to misuse of claims that the company leadership is required to return company money that has been misused.